Rifapentine With and Without Moxifloxacin for Pulmonary Tuberculosis in People With Human Immunodeficiency Virus (S31/A5349). (30th August 2022) - Pettit, April C; Phillips, Patrick P J; Kurbatova, Ekaterina; Vernon, Andrew; Nahid, Payam; Dawson, Rodney; Dooley, Kelly E; Sanne, Ian; Waja, Ziyaad; Mohapi, Lerato; Podany, Anthony T; Samaneka, Wadzanai; et al.
Abstract: Background: Tuberculosis (TB) Trials Consortium Study 31/AIDS Clinical Trials Group A5349, an international randomized open-label phase 3 noninferiority trial showed that a 4-month daily regimen substituting rifapentine for rifampin and moxifloxacin for ethambutol had noninferior efficacy and was safe for the treatment of drug-susceptible pulmonary TB (DS-PTB) compared with the standard 6-month regimen. We explored results among the prespecified subgroup of people with human immunodeficiency virus (HIV) (PWH). Methods: PWH and CD4+ counts ≥100 cells/μL were eligible if they were receiving or about to initiate efavirenz-based antiretroviral therapy (ART). Primary endpoints of TB disease-free survival 12 months after randomization (efficacy) and ≥ grade 3 adverse events (AEs) on treatment (safety) were compared, using a 6.6% noninferiority margin for efficacy. Randomization was stratified by site, pulmonary cavitation, and HIV status. PWH were enrolled in a staged fashion to support cautious evaluation of drug–drug interactions between rifapentine and efavirenz. Results: A total of 2516 participants from 13 countries in sub-Saharan Africa, Asia, and the Americas were enrolled. Among 194 (8%) microbiologically eligible PWH, the median CD4+ count was 344 cells/μL (interquartile range: 223–455). The rifapentine-moxifloxacin regimen was noninferior to control (absolute difference in unfavorable outcomes −7.4%; 95% confidence interval [CI] −20.8% to 6.0%); the rifapentine regimen was not noninferior to control (+7.5% [95% CI, −7.3% to +22.4%]). Fewer AEs were reported in rifapentine-based regimens (15%) than the control regimen (21%). Conclusions: In people with HIV-associated DS-PTB with CD4+ counts ≥100 cells/μL on efavirenz-based ART, the 4-month daily rifapentine-moxifloxacin regimen was noninferior to the 6-month control regimen and was safe. Clinical Trials Registration: NCT02410772. Abstract : In a prespecified subgroup analysis including TBTC S31/ACTG 5349 participants with HIV-associated drug-susceptible pulmonary tuberculosis on efavirenz-based therapy, the 4-month regimen substituting rifapentine for rifampin and moxifloxacin for ethambutol was safe and had noninferior efficacy compared to the 6-month control.